Macroprudential policy and intra-group dynamics: The effects of reserve requirements in Brazil - Chris Becker; Matias Ossandon Busch; Lena Tonzer (Halle Institute for Economic Research (IWH), 2020)
We examine whether liquidity dynamics within banking groups matter for the transmission of macroprudential policy. Using matched headquarter-branch data for identification, we find a lending channel of reserve requirements for municipal branches whose headquarters are more exposed to the policy tool. The result is driven by the 2008-2009 crisis and is stronger for state-owned branches, especially when being less profitable and liquidity constrained. These findings suggest the presence of cross-regional distributional effects of macroprudential policies operating via internal capital markets.
Keywords: F30; F65; G21; G28; 330; macroprudential regulation; financial intermediation; intra-group dynamics